EFFECT OF PROCUREMENT LIFECYCLE ON PERFORMANCE OF GOVERNMENT MINISTRIES IN KENYA - Okello, Tom Mboya; Kihara, Dr. Allan (International Journal of Supply Chain and Logistics, 2019)
Purpose: The purpose of the study was to establish the effect of procurement lifecycle on performance of government ministries in Kenya. The study specific objectives were to establish the effect of procurement planning on performance of Government Ministries in Kenya, to assess the effect of procurement contract award on performance of Government Ministries in Kenya and to determine the effect of procurement contract management on performance of Government Ministries in Kenya. Methodology: The study used five theories to support the literature. The study theories were Principal-Agency Theory, the Institutional Theory, Stakeholder Theory and Resource based Theory. The study employed descriptive research design. The targeted population of this study were 18 government ministries. The researcher collected primary data using both open-ended and closed-ended questionnaires. The data presentation was done using tables from both descriptive and inferential statistics analysis. The study used the multiple regression analysis models to measure the relationship between independent and dependent variables and the significant of the study. Results: R Square (R2) indicated that 51.8% of the variation on performance of government ministries could be explained by the fitted model leaving out 41.9% of variation unexplained. This indicated the presence of other factors in the surrounding, relating to procurement lifecycle towards the performance of ministries in addition to the ones identified for the study. However, the model showed goodness of fit since the R Square was above 50%. The value of the F statistic (9.146) indicates that the overall regression model was significant at the significance level of 0.05. From the finding, the study established that Tender Qualification and Selection, Procurement Contract Management and Procurement Planning were significant to the study with their P-values less than the default alpha. Procurement Contract Award was insignificant to the study with its P-value being greater that the default alpha level of significant. Contribution to policy and practice: The study recommends the Government Ministries in Kenya to consider improving procurement contract award to their suppliers by improving on the way they prepare the solicitation document, receive and evaluate bids, conducts the cost analysis, award the bid as required by the act as well as the way procurement prepares the solicitation document for better performance in future.The Government ministries to reconsider its persistence in ensuring that the procurement team develops contract administration plan, receives goods and services from the suppliers, signs the invoices to facilitate supplier payment, manages the vendors, starts up the contract in due time as required and closes the contract when it ends. By so doing, they shall ease the way in which their operational performance is conducted.